Theorizing Foreign Policy in a Globalized World
X, 254 p.
Keywords: In this collection of refreshing and provocative essays, the contributors to Theorizing Foreign Policy in a Globalized World reflect on the game-changing political impact of globalization, outlining the situation as it currently stands and suggesting strategies for analyzing foreign policy and global governance.